WHAT IS THE MEANING OF SPORT COACHING? (Expectations, possibilities, realities) - Andras S. Szabo (Sport Scientific And Practical Aspects, 2025)
In the paper information is given about important parameters, concerning the role of the coach. Special attention is paid to 10 different topics: physical and mental abilities, transfer of the knowledge, ability to manage different age groups, pedagogy, support the athletes, ready to help, motivation, outlook, behaviour. 2 dominant themes will be also briefly analysed: the main requirement from the coach (charismatic personality) and the main aim of the coaching activity (to educate healthy, stabile and happy human beings).